Highly opaque white pigment for low viscosity dispersion medium and method for producing same

JP7630423B2Active Publication Date: 2025-02-17SHISEIDO CO LTD +1
View PDF 20 Cites 0 Cited by

Patent Information

Application Number
JP2021501793
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-02-28
Filing Date
2020-01-30
Publication Date
2025-02-17
Estimated Expiration
2040-01-30

AI Technical Summary

Benefits of technology

【0015】 本開示によれば、水系分散媒のような低粘度の分散媒中においても沈降しづらく、かつ、隠蔽性にも優れる酸化チタンを主成分とする表面被覆焼成顔料を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007630423000008
    Figure 0007630423000008
  • Figure 0007630423000009
    Figure 0007630423000009
  • Figure 0007630423000010
    Figure 0007630423000010
Patent Text Reader

Abstract

Provided is a surface-coated calcination pigment which is less likely to precipitate in a low-viscosity dispersion medium such as a water-based dispersion medium, and contains, as the main component, titanium oxide that has excellent masking performance. The surface-coated calcination pigment containing titanium oxide as the main component according to the present disclosure is composed of secondary structural particles each having a surface-protruding shape, wherein each of the secondary structural particles is composed of a plurality of primary structures connected to each other, the surface of each of the secondary structural particles is coated with an inorganic material other than titanium oxide, and the each of the secondary structural particles has an equivalent circular area particle diameter of 150 to 500 nm inclusive.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a surface-coated calcined pigment containing titanium oxide as a main component, which is suitable for use in a low-viscosity dispersion medium, and a method for producing the same. [Background technology]

[0002] 2. Description of the Related Art In recent years, pigments containing titanium oxide as a main component and having various particle shapes have been blended in various dispersion media and used for various purposes.

[0003] For example, Patent Document 1 discloses that uncalcined rutile-type titanium oxide agglomerated particles having hiding properties are used in high-viscosity cosmetics. The agglomerated particles are formed by agglomerating and / or bonding fan-shaped rutile-type titanium oxide particles each having a side size of 0.05 to 0.2 μm and a thickness direction dimension of 0.02 to 0.1 μm, and the particle size of the agglomerated particles is 0.1 to 5.0 μm and the average coefficient of friction (MIU value) is 0.2 or more and less than 0.7.

[0004] Patent Documents 2 to 4 disclose that titanium oxide particles having a straw-bundle or rectangular shape are used in high-viscosity cosmetics.

[0005] Titanium oxide is widely used, primarily in cosmetics, but because it has a large Hammaker constant, which is an index of the strength of interaction, it generally tends to aggregate and settle.

[0006] Generally, the Stokes equation shown in Equation 1 below can be used to measure the settling tendency of particles in a liquid medium:

number

[0007] The average particle size of pigment-grade titanium dioxide is about 0.3 μm, and in cosmetics, the crystalline system of pigment-grade titanium dioxide is the rutile type, which has a high refractive index and is advantageous in terms of hiding power. The density of the rutile type is 4.27 g / mL (Kiyono Manabu, Titanium Dioxide, 1991). The settling velocity is proportional to the square of the particle size and the density difference, and inversely proportional to the medium viscosity, so that in a low-viscosity medium such as an aqueous dispersion medium, for example, pigment-grade titanium dioxide particles, which have a high density, tend to settle. Therefore, although such pigment-grade titanium dioxide may be blended into a medium used in cosmetics with a relatively high viscosity, it cannot be blended into a low-viscosity medium such as an aqueous dispersion medium without applying physical dispersion means such as stirring or shaking.

[0008] In addition, common pigment-grade titanium dioxide is often calcined to achieve the necessary hiding power, but calcined titanium dioxide has an increased density due to a decrease in porosity, and is therefore more prone to settling than uncalcined titanium dioxide.

[0009] In a low-viscosity dispersion medium, reducing the particle size of titanium dioxide is an effective means of improving sedimentation resistance. However, reducing the particle size of titanium dioxide reduces its hiding power, and it may no longer meet the performance requirements for use as a cosmetic ingredient. There has been a demand for a material that can provide both sedimentation resistance and hiding power in a low-viscosity dispersion medium. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Patent No. 4684970 [Patent Document 2] Patent No. 6258462 [Patent Document 3] Patent No. 5096383 [Patent Document 4] JP 2014-84251 A Summary of the Invention [Problem to be solved by the invention]

[0011] An object of the present disclosure is to provide a surface-coated calcined pigment containing titanium oxide as a main component, which is resistant to settling even in a low-viscosity dispersion medium such as an aqueous dispersion medium, and has excellent hiding properties. [Means for solving the problem]

[0012] As a result of extensive research into the dispersion of titanium oxide, the present inventors have discovered that by treating titanium oxide having a protruding shape as shown in FIG. 1 with an aqueous solution of an inorganic salt that is the raw material for the coating agent and then calcining it, a surface-coated calcined pigment composed mainly of titanium oxide can be obtained that has excellent resistance to settling in low-viscosity dispersion media and also has excellent hiding power.

[0013] The surface-coated calcined pigment containing titanium oxide as a main component according to the present disclosure can be used as a composition mixed with a dispersion medium.

[0014] <Aspect 1> A pigment mainly composed of titanium oxide, which is composed of secondary structure particles having a surface protrusion shape, the secondary structure particles being composed of a plurality of primary structures connected together, the surfaces of the secondary structure particles being coated with an inorganic material other than titanium oxide, and the area equivalent circle particle diameter being 150 nm or more and 500 nm or less. <Aspect 2> 2. The pigment of embodiment 1, wherein the inorganic material is one or more oxides of elements selected from aluminum, silicon, zinc, titanium, zirconium, iron, cerium, and tin. <Aspect 3> 2. The pigment according to embodiment 1, wherein the inorganic material is at least one selected from silicon oxide and aluminum oxide. <Aspect 4> Aspect 4. The pigment according to any one of Aspects 1 to 3, wherein the primary structures have at least one shape selected from the group consisting of needles, granules, spindles, strips, straw bunches, rods, and cocoons. <Aspect 5> The pigment has an apparent bulk density of 600 kg / m 35. The pigment of any of the preceding claims, wherein: Aspect 6 The specific surface area of ​​the pigment is 80m 2 6. The pigment of any one of the preceding embodiments, wherein the pigment has a surface area of ​​100 nm or less. Aspect 7 7. The pigment according to any one of claims 1 to 6, having a hiding power difference of 2.0 or more in a hiding power test. <Aspect 8> 8. The pigment of any one of the preceding claims, wherein the titanium oxide component is in the rutile form. <Aspect 9> A pigment according to any one of the preceding claims, wherein the pigment is for use in a cosmetic product. Aspect 10 Particle size equivalent to a circle with an area of ​​150 nm to 500 nm and 600 kg / m 3 The apparent bulk density and 80m 2 / g or less, and the surface of the pigment is covered with an oxide layer of an inorganic material other than titanium oxide. <Aspect 11> A composition comprising the pigment according to any one of aspects 1 to 10 and a dispersion medium, the composition having a viscosity of 100 mPa·s or less at a shear rate of 1000 / s. Aspect 12 A slurry containing secondary structure particles having a surface protruding shape constituted by a plurality of primary structures connected together is prepared using a titanium oxide forming solution; Add an inorganic material coating liquid, which is an aqueous solution of an inorganic salt that is a raw material of a coating agent, to the slurry; The secondary structure particles having a surface covered with an oxide layer of an inorganic material are fired in air at 550°C or higher and 750°C or lower. A method for producing the pigment according to any one of the first to tenth aspects. Effect of the Invention

[0015] According to the present disclosure, it is possible to provide a surface-coated calcined pigment containing titanium oxide as a main component, which is resistant to settling even in a low-viscosity dispersion medium such as an aqueous dispersion medium, and also has excellent hiding properties. [Brief description of the drawings]

[0016] [Figure 1] 1 is a transmission electron microscope photograph of uncoated and uncalcined titanium oxide. [Diagram 2] 1 is a transmission electron microscope photograph of uncoated titanium oxide after firing. [Diagram 3] 1 is a transmission electron microscope photograph of a surface-coated calcined pigment having as its main component titanium oxide surface-coated with silicon oxide according to one embodiment of the present disclosure after calcination. [Figure 4] FIG. 2 is a transmission electron microscope photograph of a surface-coated calcined pigment having a main component of titanium oxide surface-coated with silicon oxide and aluminum oxide according to another embodiment of the present disclosure after calcination. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present disclosure is not limited to the following embodiments, and may be modified in various ways within the scope of the present invention.

[0018] A surface-coated calcined pigment containing titanium oxide as a main component according to one embodiment of the present disclosure is composed of secondary structure particles having a surface protrusion shape as shown in FIG. 3, and these secondary structure particles are composed of a plurality of primary structures connected together, the surfaces of the secondary structure particles are coated with an inorganic material other than titanium oxide, and the area-equivalent circle particle diameter is 150 nm or more and 500 nm or less.

[0019] It is important that the secondary structure particles have a large number of surface protrusions in the pigment of the present disclosure. The pigment of the present disclosure has a low apparent bulk density due to the presence of voids caused by the protrusions as shown in Figure 3. For this reason, it is believed that the settling rate is low even in a low-viscosity dispersion medium such as an aqueous dispersion medium, making it less likely to settle than general pigment-grade titanium dioxide.

[0020] Such pigments have a unique apparent bulk density or specific surface area that differs from general pigment-grade titanium oxide, etc. It is believed that any pigment having such a unique apparent bulk density or specific surface area can exhibit the same effects.

[0021] Furthermore, the pigment of the present disclosure is produced by applying a surface coating treatment to uncalcined titanium oxide having a unique morphology as shown in Figure 1, followed by a calcination treatment. As a result, unlike the pigment described in Patent Document 2, which is produced by surface-coating titanium oxide (Figure 2) whose surface shape has been changed by calcination, the surface-coated calcined pigment of the present disclosure can maintain the unique morphology as shown in Figures 3 and 4, that is, the morphology of secondary structure particles formed by linking a plurality of primary structures. This is believed to be because a coating layer made of an inorganic material different from titanium oxide is formed on the surface of the primary structures made of titanium oxide, inhibiting sintering of the primary structures together.

[0022] Furthermore, the coating layer on the pigment surface is composed of an inorganic material other than titanium oxide. It is believed that because hydroxyl groups are easily arranged on the surface of the coating layer composed of an inorganic material, the compatibility between the aqueous dispersion medium and titanium oxide is improved, making it easier to disperse in the aqueous dispersion medium.

[0023] In addition, it is believed that the coating layer on the pigment surface has improved durability compared to an uncalcined coating layer because the binding strength with titanium oxide is improved by calcination, preventing the coating layer from peeling off.

[0024] The pigment of the present disclosure has an equivalent circle particle diameter of 150 nm to 500 nm, which is similar to that of general pigment-grade titanium dioxide, and is calcined after surface coating treatment. As a result, compared with uncalcined surface-coated titanium dioxide as described in Patent Documents 1, 3, and 4, it is possible to reduce the porosity of the pigment, particularly the porosity near the core inside the pigment, which is difficult to coat with, and therefore it is believed that the hiding performance can be further improved.

[0025] <<Surface-coated calcined pigment with titanium dioxide as the main component>> The surface-coated calcined pigment (sometimes simply referred to as "pigment") having titanium oxide as a main component according to the present disclosure includes a pigment having a secondary structure particle mainly composed of titanium oxide, the surface of which is coated with an inorganic material other than titanium oxide, has an equivalent circle area particle diameter of 150 nm or more and 500 nm or less, and has a surface protruding shape constituted by a plurality of primary structures connected together, and / or a pigment having a surface roughness of 600 kg / m 3 The apparent bulk density and 80m 2 A pigment containing titanium oxide as a main component and having at least one specific surface area selected from the group consisting of titanium oxide having a specific surface area of ​​0.1 to 1.0 nm / g or less can be used.

[0026] The type of titanium oxide component in the pigment may be any of anatase type, rutile type, and brookite type, but from the viewpoint of hiding power, rutile type titanium oxide is preferred.

[0027] <Characteristics of pigments> (Equivalent circle particle size) The circle-equivalent particle diameter of a pigment can mean, for example, the particle diameter when converted into a circular particle having the same area as the projected area of ​​the pigment observed by a transmission electron microscope. The circle-equivalent particle diameter can be defined as the average value of 10 or more particles. The circle-equivalent particle diameter of titanium oxide particles is preferably a size of about 1 / 2 the wavelength of visible light, more preferably 150 nm or more and 450 nm or less, and particularly preferably 200 nm or more and 400 nm or less, in order to enhance the scattering effect of visible light and enhance the hiding power.

[0028] (Apparent bulk density) The pigment of the present disclosure has an apparent bulk density of 600 kg / m or less in order to reduce the settling rate. 3 The apparent bulk density is preferably less than or equal to 100 kg / m. There is no particular lower limit for the apparent bulk density. 3 The apparent bulk density can be determined, for example, by using a specific volume tester as described below.

[0029] (specific surface area) The pigment of the present disclosure has a specific surface area of ​​80 m from the viewpoints of hiding power, resistance to sedimentation, etc. 2 The specific surface area of ​​titanium oxide can be determined, for example, by the BET method.

[0030] (Concealment) In the hiding power test described below, the pigment of the present disclosure can have a color difference (ΔE), which is an index of hiding power, of, for example, 30.0 or less, 27.0 or less, 25.0 or less, 24.0 or less, or 23.0 or less. There is no particular restriction on the lower limit of the color difference, but it can be specified, for example, as 10.0 or more, 12.0 or more, or 15.0 or more.

[0031] In addition, the pigment of the present disclosure can be evaluated for hiding power in a hiding power test described later, based on the color difference of titanium oxide that has not been surface-coated or calcined, from the difference in color difference (hiding power difference) between the titanium oxide and other titanium oxides. This hiding power difference can be specified as 2.0 or more. There is no particular limit to the upper limit of the hiding power difference, but it can be specified as 20.0 or less, for example.

[0032] (Crystallite size) The pigment of the present disclosure desirably has a crystallite diameter of 8.0 nm or more, and desirably has a crystallite diameter of 25.0 nm or less. The crystallite diameter of titanium oxide can be measured by a general X-ray diffraction method.

[0033] (shape) The pigment of the present disclosure may have secondary particles having a surface protruding shape formed by linking a plurality of primary structures.

[0034] The shape of the primary structure may be any shape that provides resistance to settling and hiding performance, and may be, but is not limited to, at least one selected from needles, granules, spindles, short shapes, straw bundles, rods, and cocoons. Of these, needles or rods as shown in Figures 3 and 4 are preferred.

[0035] The primary structures are connected so as to present a protruding shape on the surface of the secondary structure particle, and the connection structure is not particularly limited. For example, the primary structures may be connected in a fan-like, radial, or random manner, and among these, it is preferable that the primary structures are connected radially from the viewpoint of sedimentation resistance and hiding ability.

[0036] <Surface coating layer> The pigment of the present disclosure has its surface coated with one or more inorganic materials other than titanium oxide. Such inorganic materials include, but are not limited to, components containing elements selected from aluminum, silicon, zinc, zirconium, iron, cerium and tin, such as oxides of the above elements. Among them, silicon oxide and aluminum oxide are preferred, and silicon oxide is more preferred. From the viewpoint of hiding power, it is preferred that the pigment having a surface coating layer is mainly made of titanium oxide, that is, 800 g / kg or more of titanium oxide components. The ratio of the surface coating layer in such titanium oxide can be 200 g / kg or less, and 10 g / kg or more, based on the mass of the pigment.

[0037] By coating the surface of the pigment of the present disclosure with an inorganic material other than titanium oxide, it is possible to reduce the change in shape caused by sintering of the primary structure, and also to improve the dispersibility in a dispersion medium, particularly an aqueous dispersion medium.

[0038] <<Composition containing surface-coated calcined titanium oxide>> The pigment having titanium oxide as a main component according to the present disclosure can constitute a composition together with a low viscosity dispersion medium, particularly an aqueous dispersion medium.

[0039] Characteristics of the Composition (viscosity) A composition containing the pigment of the present disclosure may have a viscosity of 100 mPa·s or less at a shear rate of 1000 / s. Such a viscosity can be measured using a rheometer such as an MCR-302 (manufactured by Anton-Paar), and the viscosity of the object being measured at 32°C and 1 atmosphere at a shear rate of 1000 / s may be specified as 100 mPa·s or less, 50 mPa·s or less, or 10 mPa·s or less, or may be specified as 1 mPa·s or more, 2 mPa·s or more, or 3 mPa·s or more.

[0040] The static viscosity of the composition of the present disclosure, i.e., the viscosity at a shear rate as close to 0s -1 For example, the viscosity at a shear rate of 1 / s can be specified as 1000 mPa s or less, or 10 mPa s or more. The static viscosity can also be measured using the above-mentioned rheometer under conditions of 32°C and 1 atm.

[0041] (Sedimentation resistance) In the sedimentation resistance test described below, the composition of the present disclosure can achieve 90.0% or more, 93.0% or more, or 95.0% or more after 24 hours, and can also achieve 100% or less, less than 100%, or 99.0% or less.

[0042] (Sedimentation resistance) The composition of the present disclosure can achieve 90.0% or more after 24 hours in a sedimentation resistance test described below, and can also achieve 85.0% or more even after 90 hours.

[0043] <Pigment content> The amount of pigment in the composition can be adjusted appropriately depending on the intended use, etc., and is not limited to the following amounts, but can be, for example, 50 g / kg or more, 100 g / kg or more, or 200 g / kg or more, and can be 300 g / kg or less, 270 g / kg or less, or 250 g / kg or less.

[0044] <Dispersion medium> The dispersion medium is not particularly limited as long as it can disperse the pigment, and one or more of known dispersion media such as organic dispersion media and aqueous dispersion media can be used. Among them, it is preferable to use an aqueous dispersion medium. Examples of the aqueous dispersion medium include water, various alcohols such as lower alcohols and polyhydric alcohols, and mixtures thereof.

[0045] Examples of the lower alcohol include ethanol, propanol, isopropanol, isobutyl alcohol, and t-butyl alcohol.

[0046] Examples of polyhydric alcohols include dihydric alcohols (e.g., ethylene glycol, propylene glycol, trimethylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, tetramethylene glycol, 2,3-butylene glycol, pentamethylene glycol, 2-butene-1,4-diol, hexylene glycol, octylene glycol, etc.); trihydric alcohols (e.g., glycerin, trimethylolpropane, etc.); tetrahydric alcohols (e.g., pentaerythritol such as 1,2,6-hexanetriol, etc.); pentahydric alcohols (e.g., xylitol, etc.); hexahydric alcohols (e.g., sorbitol, mannitol, etc.); polyhydric alcohol polymers (e.g., diethylene glycol, dipropylene glycol, triethylene glycol, glycol, polypropylene glycol, tetraethylene glycol, diglycerin, polyethylene glycol, triglycerin, tetraglycerin, polyglycerin, etc.); dihydric alcohol alkyl ethers (e.g., ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, ethylene glycol monophenyl ether, ethylene glycol monohexyl ether, ethylene glycol mono-2-methylhexyl ether, ethylene glycol isoamyl ether, ethylene glycol benzyl ether, ethylene glycol isopropyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, etc.);Dihydric alcohol alkyl ethers (e.g., diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol butyl ether, diethylene glycol methyl ethyl ether, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, propylene glycol isopropyl ether, dipropylene glycol methyl ether, dipropylene glycol ethyl ether, dipropylene glycol butyl ether, etc.); dihydric alcohol ether esters (e.g., ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, ethylene glycol monophenyl ether acetate, ethylene glycol diadipate, ethylene glycol disuccinate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, propylene glycol monophenyl ether acetate, etc.; glycerin monoalkyl ethers (e.g., xyl alcohol, selachyl alcohol, batyl alcohol, etc.); sugar alcohols (e.g., sorbitol, maltitol, maltotriose, mannitol, sucrose, erythritol, glucose, fructose, starch decomposition sugar, maltose, xylitose, starch decomposition sugar reduced alcohol, etc.); glycerin solids; tetrahydrofurfuryl alcohol; POE-tetrahydrofurfuryl alcohol; POP-butyl ether; POP·POE-butyl ether; tripolyoxypropylene glycerin ether; POP-glycerin ether; POP-glycerin ether phosphate; POP·POE-pentane erythritol ether, polyglycerin, etc.;

[0047] <Optional ingredients> The composition of the present disclosure may contain other components, such as pigments other than titanium oxide, dyes, esters, moisturizing agents, water-soluble polymers, oils, higher alcohols, binders, dispersants, various salt components, thickeners, surface tension reducers such as various surfactants, film agents, ultraviolet absorbers, ultraviolet scattering agents, metal ion sequestering agents, amino acids, organic amines, polymer emulsions, pH adjusters, skin nutrients, vitamins, antioxidants, antioxidant assistants, fragrances, preservatives, anti-inflammatory agents, anti-inflammatory agents, whitening agents, activators, antiseborrheic agents, various herbal extracts, drugs, etc., as necessary, within the scope that does not inhibit the effects of the present disclosure. The pigment of the present disclosure has excellent sedimentation resistance, so it is not necessary to use a dispersant, but when a dispersant such as a polyelectrolyte is used, the sedimentation resistance can be further improved.

[0048] 《Application》 The surface-coated calcined pigment containing titanium oxide as a main component according to the present disclosure and compositions containing the pigment according to the present disclosure can be used appropriately in a wide range of applications, such as cosmetics, paints, and inks.

[0049] <<Method for producing surface-coated calcined pigment mainly composed of titanium oxide>> There is no particular restriction on the method of producing the surface-coated calcined pigment mainly composed of titanium oxide of the present disclosure. For the method of producing uncalcined titanium oxide without surface coating as shown in FIG. 1, for example, the description in Patent Document 1 can be referred to. Specifically, for example, a titanyl sulfate solution is used as a titanium oxide forming solution, and the titanyl sulfate solution is neutralized with alkali at a temperature of 10° C. or less to obtain orthotitanic acid, to which hydrochloric acid is added at a temperature of 10° C. or less to completely dissolve the orthotitanic acid, and then heated to perform hydrolysis, thereby obtaining uncalcined titanium oxide without surface coating, which is a secondary structure particle in which needle-shaped primary structures are connected as shown in FIG. 1. The TiO2 concentration at that time is 50 g / L or more and 140 g / L or less, preferably 60 g / L or more and 120 g / L or less, and the hydrochloric acid concentration is 70 g / L or more and 170 g / L or less, preferably 80 g / L or more and 160 g / L or less. The temperature of hydrolysis is 25° C. or more and 60° C. or less, preferably 30° C. or more and 55° C. or less.

[0050] In addition, unsintered titanium oxide without a surface coating, as shown in Figure 1, can also be obtained by hydrolysis using, in addition to orthotitanic acid, a titanium tetrachloride solution or a solution in which an alkali salt of titanic acid obtained by treating metatitanic acid with an alkali is dissolved in hydrochloric acid.

[0051] In addition, unsintered titanium oxide having a secondary structure in which primary structures such as straw bundles or strips are connected and not surface-coated can be obtained by appropriately using the methods described in Patent Documents 3 and 4, and by heating or firing as necessary.

[0052] The method of surface-coating the unsintered titanium oxide that has not been surface-coated is not particularly limited, but for example, the titanium oxide prepared as described above is added to ion-exchanged water to prepare a slurry. Next, an inorganic material coating liquid consisting of an aqueous solution of sodium silicate is slowly added while stirring the slurry while keeping it at 70°C, and after stirring for a predetermined time, an acid such as dilute hydrochloric acid or dilute sulfuric acid is added to adjust the pH to 5.0 to 8.0. By carrying out this operation two or more times, the layer structure or coating amount of the surface coating layer can be adjusted. The coating amount of the surface coating layer can also be adjusted by adjusting the composition, concentration, and blending amount of the inorganic material coating liquid.

[0053] The resulting slurry is filtered, washed with water, dried, and calcined in a muffle furnace or rotary kiln, which is a common calcination furnace, to obtain a surface-coated calcined pigment containing titanium oxide as a main component, having a shape as shown in Figures 3 and 4. The calcination temperature can be, for example, from 500°C to 800°C, and more preferably from 550°C to 750°C, and the calcination time can be from 0.5 to 2.0 hours, and more preferably from 1.0 to 1.5 hours.

[0054] When uncalcined titanium oxide that has not been surface-coated is calcined, the morphology generally changes from that shown in Fig. 1 to that shown in Fig. 2. However, when titanium oxide that has been surface-coated with an inorganic material is calcined, the particle shape of the titanium oxide can substantially maintain the shape shown in Fig. 1, as shown in Figs. 3 and 4.

[0055] In the pigment of the present disclosure, the performance such as retention of the surface protrusion shape, resistance to sedimentation, and hiding power can be controlled by appropriately adjusting, for example, the material of the surface coating layer, the firing temperature, the firing time, and the like. EXAMPLES

[0056] The present disclosure will be described in more detail below with reference to examples, but the present disclosure is not limited thereto. In the following, unless otherwise specified, the blending amount is shown in g / kg.

[0057] Examples 1 to 3 and Comparative Examples 1 to 5 The surface-coated calcined pigments containing titanium dioxide as the main component, obtained by the manufacturing method shown below, were evaluated for their area circle equivalent particle size, specific surface area, apparent bulk density, crystallite size, and hiding power. The compositions obtained by the formulations and manufacturing methods shown in Table 1 below were also evaluated for their viscosity and sedimentation resistance. In Table 1, the amount of SiO2 coated on uncalcined titanium dioxide that has not been surface-coated is indicated as "coating amount," and those that have been calcined are indicated as "yes," and those that have not been calcined are indicated as "no."

[0058] Evaluation of pigments The prepared pigments were subjected to various evaluations shown below, and the results are summarized in Table 1.

[0059] (Evaluation of particle size equivalent to circle area) The area-equivalent circle particle diameter was evaluated using a transmission electron microscope, Model H7100 (Hitachi High-Technologies Corporation), at 100,000 times magnification, as the average value of 10 titanium dioxide particles.

[0060] (Evaluation of specific surface area) The specific surface area was evaluated by the BET method using a Macsorb HM model-1208 (manufactured by Mountech).

[0061] (Evaluation of apparent bulk density) Approximately 10 mL of pigment was placed in a 20 mL specific volume test tube and weighed. Using a specific volume tester TAP-ONE TP01 (manufactured by Yamaguchi Mica Co., Ltd.), the weighed test tube was tapped 200 times, after which the volume was measured and the apparent bulk density was calculated. The apparent bulk density was also evaluated according to the following criteria.

[0062] A: Apparent bulk density ≦500kg / m 3 B: 500kg / m 3 < Apparent bulk density ≦ 600kg / m 3 C: 600kg / m 3 <Apparent bulk density

[0063] (Evaluation of crystallite size) The crystallite size of titanium dioxide was measured using an X-ray diffractometer (Geigerflex, manufactured by Rigaku Denki Co., Ltd.), and the average crystallite size was calculated by applying the Scherrer equation.

[0064] (Evaluation of Concealment) Titanium dioxide was mixed and stirred into nitrocellulose lacquer so that the pigment ratio was 50 g / kg to prepare a slurry. The slurry was then applied with a 0.101 mm applicator onto a black and white hiding rate test paper described in JIS K5400 and dried to obtain a test sample. The obtained test sample was measured for the coating film surface on the white and black paper using a spectrophotometer CM-2600d (manufactured by Konica Minolta). The color difference (ΔE) in the Hunter Lab color space was calculated from the following formula 2, and the difference (hiding power difference) between the color difference of titanium dioxide that was not surface-coated and calcined and the color difference of each of the other pigments was calculated from the following formula 3, and the hiding power was evaluated according to the following criteria:

number

[0065] In addition, a larger hiding power difference, particularly a hiding power difference of 2.0 or more, indicates improved hiding property.

[0066] A: 4.0≦ hiding power difference B: 2.0≦Hiding power difference<4.0 C: Hiding power difference <2.0

[0067] Evaluation of the Composition The prepared compositions were subjected to various evaluations shown below, and the results are summarized in Table 1.

[0068] (Viscosity evaluation) The viscosity was evaluated using MCR-302 (manufactured by Anton-Paar). The viscosity was measured at 32° C. and 1 atm, and the shear rate of the measurement object was 1000 / s.

[0069] (Evaluation of Sedimentation Resistance) A dispersion for evaluation was prepared by adding 0.1 g of pigment to a 50 mL colorimetric test tube, then adding ion-exchanged water to make 30 mL, and shaking vigorously to disperse the titanium dioxide. The settling state of the pigment after a specified time had elapsed was calculated as a percentage by calculating the ratio of the height of the settling interface to the height of the water surface of the dispersion, and the results are summarized in Table 1. The larger the value, particularly 90.0% or more after 24 hours and 85.0% or more after 90 hours, the better the settling resistance.

[0070] Example 1 (Process for forming uncalcined titanium dioxide without surface coating) The titanyl sulfate solution obtained by dissolving the washed metatitanic acid in sulfuric acid was slowly dropped into a 160 g / L sodium carbonate solution so that the liquid temperature did not exceed 10°C, and the dropping of titanyl sulfate was stopped when the pH reached 10.0. The resulting white precipitate was filtered by a conventional method and thoroughly washed to obtain orthotitanic acid.

[0071] Next, while cooling to below 10°C, the washed orthotitanic acid cake was added to concentrated hydrochloric acid and stirred until the orthotitanic acid was completely dissolved. Thereafter, the TiO2 concentration was adjusted to 60 g / L and the hydrochloric acid concentration to 80 g / L, and the mixture was heated with stirring to adjust the liquid temperature to 55°C and stirred for 20 hours to carry out hydrolysis. The obtained slurry was neutralized, washed in a conventional manner, and dried to obtain titanium dioxide A, which has a secondary structure particle form composed of connected needle-like primary structures as shown in Figure 1.

[0072] (Formation process of surface-coated calcined pigments mainly composed of titanium dioxide) The obtained uncalcined titanium dioxide A without surface coating was dispersed in ion-exchanged water to prepare a dispersion. Next, 50 g / kg of sodium silicate aqueous solution calculated as SiO2 was added to the dispersion containing titanium dioxide A while stirring, and after stirring for 1 hour, dilute hydrochloric acid was slowly added to adjust the pH to 5.0. Here, the amount of sodium silicate solution was used in an amount that would result in a SiO2 coating of 33 g / kg, based on the mass of titanium dioxide A before coating. The obtained dispersion was filtered, washed with water, and dried in a conventional manner to obtain uncalcined titanium dioxide B with a surface coating.

[0073] Next, this surface-coated uncalcined titanium dioxide B was calcined in a muffle furnace at 550°C for 1 hour to obtain surface-coated calcined rutile-type titanium dioxide C. As shown in Figure 3, the particle shape of the resulting calcined titanium dioxide C, even after calcination, exhibited a shape with protrusions on the surface that was nearly identical to the shape of the uncalcined titanium dioxide A in Figure 1 that was not surface-coated.

[0074] The calcined titanium dioxide C thus obtained was added to ion-exchanged water in the mixing ratio shown in Table 1 below, and the mixture was vigorously shaken to prepare a composition.

[0075] Example 2 Surface-coated calcined titanium dioxide D was prepared in the same manner as in Example 1, except that the amount of SiO2 coating was changed from 33 g / kg to 20 g / kg. Using this surface-coated calcined titanium dioxide D, a composition of Example 2 was prepared in the same manner as in Example 1.

[0076] Example 3 Surface-coated calcined rutile-type titanium dioxide E was prepared in the same manner as in Example 1, except that the amount of SiO2 coating was changed from 33 g / kg to 47 g / kg. Using this titanium dioxide E, the composition of Example 3 was prepared in the same manner as in Example 1.

[0077] Comparative Example 1 Titanium dioxide A that was not surface-coated or calcined was prepared by the same method as in the titanium dioxide formation process in Example 1. Next, the obtained titanium dioxide A was added to ion-exchanged water in the blending ratio shown in Table 1 below, and the mixture was vigorously shaken to prepare the composition of Comparative Example 1.

[0078] Comparative Example 2 Titanium dioxide A that was not surface-coated and calcined, prepared by the same method as in the step of forming titanium dioxide that was not surface-treated and calcined in Example 1, was calcined in a muffle furnace at 550°C for 1 hour to prepare calcined titanium dioxide F that was not surface-coated. Next, titanium dioxide F was added to ion-exchanged water in the blending ratio shown in Table 1 below, and the mixture was vigorously shaken to prepare the composition of Comparative Example 2.

[0079] Comparative Example 3 Surface-treated titanium dioxide B that was not calcined after surface coating was prepared by the same methods as those for forming titanium dioxide that was not surface-treated and calcined and for forming surface-coated titanium dioxide in Example 1. Next, the obtained titanium dioxide B was added to ion-exchanged water in the blending ratio shown in Table 1 below, and the mixture was vigorously shaken to prepare a composition of Comparative Example 3.

[0080] Comparative Example 4 The composition of Comparative Example 4 was prepared by adding TIPAQUE (trademark) CR-50 (manufactured by Ishihara Sangyo Kaisha), which is a pigment-grade rutile-type titanium dioxide having an irregular particle shape, to ion-exchanged water in the blending ratio shown in Table 1 below and shaking vigorously.

[0081] Comparative Example 5 The composition of Comparative Example 5 was prepared by adding TTO-55(A) (manufactured by Ishihara Sangyo Kaisha), which is a fine particle type rutile titanium dioxide having a needle-like particle shape, to ion-exchanged water in the blending ratio shown in Table 1 below and shaking vigorously.

[0082] [Table 1]

[0083] <result> As is clear from the results of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it was confirmed that coating the surface of titanium dioxide with an inorganic material improves sedimentation resistance.

[0084] Furthermore, from the measurement results of Examples 1 to 3 and Comparative Example 3, it became clear that in order to achieve a hiding power difference of 2.0 or more, it is necessary to calcinate titanium dioxide whose surface is coated with an inorganic material.

[0085] By coating titanium dioxide with an inorganic material and then baking it, we were able to obtain titanium dioxide that has excellent resistance to settling and a hiding power difference of 2.0 or more.

Claims

1. It is composed of secondary structure particles having a surface protrusion shape, The secondary structure particle is formed by connecting a plurality of primary structures, the secondary structure particles have surfaces coated with a fired oxide layer of an inorganic material other than titanium oxide, and have an area-equivalent circle diameter of 150 nm or more and 500 nm or less; the inorganic material is one or more oxides of elements selected from aluminum, silicon, zinc, zirconium, cerium, and tin; In the following hiding power test, the color difference (ΔE) is 30.0 or less or the hiding power difference is 2.0 or more. Surface-coated calcined pigments mainly composed of rutile-type titanium oxide (excluding rutile-type titanium oxide having a strip-like particle shape in which the major axis of each particle is oriented and aggregated in the minor axis direction and has an average particle diameter D50 of 100 nm to 400 nm, and coated titanium oxide powders having layers of silicon oxide or hydroxide, aluminum oxide or hydroxide, and iron oxide or hydroxide): Concealment test The pigment is mixed and stirred into a nitrocellulose lacquer so that the ratio of the pigment is 50 g / kg to prepare a slurry. The slurry is then applied to a black and white hiding power test paper described in JIS K5400 using a 0.101 mm applicator and dried to prepare a test sample. The coating film surfaces on the white and black papers of the hiding power test paper of this test sample are measured using a spectrophotometer, and the color difference (ΔE) in the Hunter Lab color space is calculated from the following formula 2, or the hiding power difference is calculated from the following formula 3: [0010] Hiding power difference=(color difference (ΔE) of uncalcined titanium oxide that has not been surface-coated or calcined)−(color difference (ΔE) of the pigment) Equation 3

2. It is composed of secondary structure particles having a surface protrusion shape, The secondary structure particle is formed by connecting a plurality of primary structures, the secondary structure particles have surfaces coated with a fired oxide layer of an inorganic material other than titanium oxide, and have an area-equivalent circle diameter of 150 nm or more and 500 nm or less; the inorganic material is one or more oxides of elements selected from aluminum, silicon, zinc, zirconium, cerium, and tin; In the following hiding power test, the color difference (ΔE) is 30.0 or less or the hiding power difference is 2.0 or more. Cosmetic surface-coated calcined pigments mainly composed of rutile-type titanium dioxide (excluding coated titanium dioxide powders having layers of silicon oxide or hydroxide, aluminum oxide or hydroxide, and iron oxide or hydroxide): Concealment test The pigment is mixed and stirred into a nitrocellulose lacquer so that the ratio of the pigment is 50 g / kg to prepare a slurry. The slurry is then applied to a black and white hiding power test paper described in JIS K5400 using a 0.101 mm applicator and dried to prepare a test sample. The coating film surfaces on the white and black papers of the hiding power test paper of this test sample are measured using a spectrophotometer, and the color difference (ΔE) in the Hunter Lab color space is calculated from the following formula 2, or the hiding power difference is calculated from the following formula 3: [0025] Hiding power difference=(color difference (ΔE) of uncalcined titanium oxide that has not been surface-coated or calcined)−(color difference (ΔE) of the pigment) Equation 3

3. 3. The pigment according to claim 1, wherein the inorganic material is at least one selected from the group consisting of silicon oxide and aluminum oxide.

4. The pigment according to claim 1 , wherein the primary structures have at least one shape selected from the group consisting of needles, granules, spindles, strips, straw bundles, rods, and cocoons.

5. The apparent bulk density of the pigment is 600 kg / m 3 5. The pigment according to claim 1 , wherein

6. The specific surface area of ​​the pigment is 80 m 2 The pigment according to claim 1 , wherein the molecular weight of the pigment is less than or equal to 1 / g.

7. The pigment according to claim 1 or any one of claims 3 to 6, which is for use in cosmetics.

8. A particle size equivalent to a circle having an area of ​​150 nm or more and 500 nm or less, 600 kg / m 3 Apparent bulk density of 34 m 2 / g or more and 80 m 2 / g or less specific surface area, and In the following hiding power test, it has a color difference (ΔE) of 30.0 or less or a hiding power difference of 2.0 or more, and The surface is covered with a fired oxide layer of an inorganic material other than titanium oxide, and the inorganic material is one or more oxides of elements selected from aluminum, silicon, zinc, zirconium, cerium and tin. Surface-coated calcined pigments mainly composed of rutile-type titanium oxide (excluding rutile-type titanium oxide having a strip-like particle shape in which the major axis of each particle is oriented and aggregated in the minor axis direction and has an average particle diameter D50 of 100 nm to 400 nm, and coated titanium oxide powders having layers of silicon oxide or hydroxide, aluminum oxide or hydroxide, and iron oxide or hydroxide): Concealment test The pigment is mixed and stirred into a nitrocellulose lacquer so that the ratio of the pigment is 50 g / kg to prepare a slurry. The slurry is then applied to a black and white hiding power test paper described in JIS K5400 using a 0.101 mm applicator and dried to prepare a test sample. The coating film surfaces on the white and black papers of the hiding power test paper of this test sample are measured using a spectrophotometer, and the color difference (ΔE) in the Hunter Lab color space is calculated from the following formula 2, or the hiding power difference is calculated from the following formula 3: [0030] Hiding power difference=(color difference (ΔE) of uncalcined titanium oxide that has not been surface-coated or calcined)−(color difference (ΔE) of the pigment) Equation 3

9. A particle size equivalent to a circle having an area of ​​150 nm or more and 500 nm or less, 600 kg / m 3 Apparent bulk density of 34 m 2 / g or more and 80 m 2 / g or less specific surface area, and In the following hiding power test, it has a color difference (ΔE) of 30.0 or less or a hiding power difference of 2.0 or more, and The surface is covered with a fired oxide layer of an inorganic material other than titanium oxide, and the inorganic material is one or more oxides of elements selected from aluminum, silicon, zinc, zirconium, cerium and tin. Cosmetic surface-coated calcined pigments mainly composed of rutile-type titanium dioxide (excluding coated titanium dioxide powders having layers of silicon oxide or hydroxide, aluminum oxide or hydroxide, and iron oxide or hydroxide): Concealment test The pigment is mixed and stirred into a nitrocellulose lacquer so that the ratio of the pigment is 50 g / kg to prepare a slurry. The slurry is then applied to a black and white hiding power test paper described in JIS K5400 using a 0.101 mm applicator and dried to prepare a test sample. The coating film surfaces on the white and black papers of the hiding power test paper of this test sample are measured using a spectrophotometer, and the color difference (ΔE) in the Hunter Lab color space is calculated from the following formula 2, or the hiding power difference is calculated from the following formula 3: [0045] Hiding power difference=(color difference (ΔE) of uncalcined titanium oxide that has not been surface-coated or calcined)−(color difference (ΔE) of the pigment) Equation 3

10. A composition comprising the pigment according to any one of claims 1 to 9 and a dispersion medium, and having a viscosity of 100 mPa·s or less at a shear rate of 1000 / s.

11. 10. A method for producing a pigment according to claim 1, comprising the steps of: using a titanium oxide forming solution to prepare a slurry containing secondary structure particles having a surface-protruding shape constituted by a plurality of primary structures linked together; adding an inorganic material coating liquid comprising an aqueous solution of an inorganic salt that is a raw material for a coating agent to the slurry; and calcining the secondary structure particles whose surfaces are coated with the inorganic material at a temperature of 550° C. or higher and 750° C. or lower in air.

Citation Information

Patent Citations

  • JP1975096383A

  • Noise eliminating circuit

    JP1987058462A

  • Coagulated titanium dioxide and production thereof

    JP1990283617A

  • Dendritic or asteroid titanium dioxide fine particle and production thereof

    JP1995165423A

  • Rutile-type titanium dioxide particle and its production

    JP1997202620A